Boswellic Acid and Cisplatin Synergy: A Promising Approach to Enhance Chemosensitivity in Lung Cancer Therapy - Mohammed Abdalla Hussein; Reham Mahmoud Abdel Moneim; Amira Emad Hamdy; Elarya Armanuoos Fawzy; Alaa Mohamed Ismail; Eman Abdelrahman Mohamed; Nawal Ibrahim El-Adl (Current Bioactive Compounds, 2025)
Introduction: Lung cancer maintains its devastating position as the most fatal malignancy globally, responsible for nearly 1 in 5 cancer deaths according to recent WHO reports. The search for innovative solutions has led our research team to investigate boswellic acid, a bioactive component isolated from the resin of Boswellia serrata trees that has demonstrated remarkable cytotoxic properties in our preliminary laboratory tests. Our investigation had two primary goals: first, to examine how boswellic acid influences A549 lung adenocarcinoma cell survival when administered alone; and second, to evaluate its potential to enhance cisplatin effectiveness through combination therapy, with particular attention to mechanisms involving drug resistance genes and oxidative stress pathways. Methods: We conducted comprehensive in vitro experiments using: A549 cell line cultured under standard conditions. Treatment concentrations optimized through dose-response curves (boswellic acid: 80.58 μg/mL; cisplatin: 77.33 μg/mL). Combination exposure for 48 hours followed by multiple assessments: Cell viability measurements via MTT colorimetric assay, detailed cell cycle analysis using flow cytometry with PI staining, oxidative stress evaluation through GSH and antioxidant enzyme assays, gene expression profiling of ABCC1 and NQO1 via qPCR, and molecular docking simulations to predict protein interactions. Results: Boswellic acid alone achieved an IC50 at 80.58 μg/mL. Cisplatin alone showed an IC50 at 77.33 μg/mL. Combination treatment demonstrated synergistic action, reducing viable cells to just 32.64%. Boswellic acid increased G1 (47.41%), S (25.08%), and G2-M (7.79%) phases. Cisplatin primarily induced G1 arrest (45.43%). The combination produced unique cell cycle distribution patterns. Strong binding affinity of boswellic acid to ABCC1/NQO1 proteins. Unexpected gene expression patterns despite binding predictions Discussion: The synergistic effects of boswellic acid and cisplatin highlight its potential in overcoming chemoresistance. However, validation in multiple cell lines and in vivo models is essential to confirm its broader applicability. The study acknowledges limitations, including the exclusive use of a single cell line and the need for further protein-level validation. Conclusion: These laboratory findings position boswellic acid as a promising candidate for combination therapy with cisplatin, potentially offering new strategies to overcome chemoresistance in lung cancer treatment. While these in vitro results are encouraging, we recognize the need for additional studies using animal models and eventual clinical trials to validate these observations.